Uncovering the Impact of Leverage, Liquidity, and Firm Size on Infrastructure Firms’ Profitability - Wahyudi, Haris; Sumiati (Jurnal Management Risiko dan Keuangan, 2025)
The infrastructure sector is one of the national development priority sectors that has experienced significant growth, both in terms of investment and economic output, as reflected in the upward trend of the sector's real GDP since 2021. However, amid this growth, the financial performance of companies in the infrastructure sector has shown a fluctuating trend and has not fully recovered, particularly when viewed through profitability indicators such as Return on Assets (ROA), which remains lower compared to the average of all sectors listed on the Indonesia Stock Exchange (IDX). This study aims to examine and analyze the effect of leverage, liquidity, and firm size on profitability in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. This research uses a quantitative approach. The data utilized are secondary data in the form of financial statements from infrastructure sector companies listed on the IDX during 2019-2023 and information from each company’s official website. The sampling method used is census sampling with predetermined criteria, resulting in a sample of 22 companies. The analysis method employed is multiple linear regression using SPSS version 27. After conducting classical assumption tests, 3 companies were excluded as outliers, leaving 18 companies for the multiple linear regression analysis. The results show that leverage and liquidity have a significant effect on profitability, while firm size does not have a significant effect on profitability. Theoretically, this research supports the capital structure theory and the trade-off theory. Abstrak: Sektor infrastruktur merupakan salah satu sektor prioritas pembangunan nasional yang mengalami pertumbuhan signifikan, baik dari sisi investasi maupun output ekonomi, sebagaimana tercermin dalam tren peningkatan PDB riil sektor ini sejak 2021. Namun, di tengah pertumbuhan tersebut, kinerja keuangan perusahaan di sektor infrastruktur justru menunjukkan tren fluktuatif dan belum sepenuhnya pulih, terutama dilihat dari indikator profitabilitas seperti ROA yang masih lebih rendah dibandingkan rata-rata seluruh sektor di BEI. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh Leverage, Likuiditas, dan Ukuran perusahaan terhadap Profitabilitas pada perusahaan sektor infrastruktur yang terdaftar di BEI periode tahun 2019-2023. Jenis penelitian yang digunakan adalah penelitian kuantitatif. Data yang digunakan dalam penelitian ini adalah data sekunder berupa laporan keuangan perusahaan sektor infrastruktur yang terdaftar di BEI periode tahun 2019-2023 dan masing-masing website perusahaan. Pemilihan sampel menggunakan metode sampel sensus atau sampling jenuh dengan kriteria yang sudah ditentukan sehingga diperoleh sampel sebanyak 22 perusahaan. Metode analisis yang digunakan ialah analisis regresi linier berganda dengan bantuan program SPSS versi 27. Terdapat pengurangan sampel sebanyak 3 perusahaan (sebagai oulier) atas hasil uji asumsi klasik sehingga jumlah sampel menjadi 18 perusahaan yang dilakukan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa Leverage dan Likuiditas berpengaruh signifikan terhadap profitabilitas, sedangkan, Ukuran perusahaan tidak berpengaruh signifikan terhadap profitabilitas. Penelitian ini secara teoritis mendukung teori struktur modal, serta teori trade-off.